Urinary metals and leukocyte telomere length in American Indian communities: The Strong Heart and the Strong Heart Family Study. (March 2019) - Grau-Perez, Maria; Zhao, Jinying; Pierce, Brandon; Francesconi, Kevin A.; Goessler, Walter; Zhu, Yun; An, Qiang; Umans, Jason; Best, Lyle; Cole, Shelley A.; Navas-Acien, Ana; Tellez-Plaza, Maria
Abstract: Introduction: While several mechanisms may explain metal-related health effects, the exact cellular processes are not fully understood. We evaluated the association between leukocyte telomere length (LTL) and urine arsenic (ΣAs), cadmium (Cd) and tungsten (W) exposure in the Strong Heart Study (SHS, N = 1702) and in the Strong Heart Family Study (SHFS, N = 1793). Methods: Urine metal concentrations were measured using ICP-MS. Arsenic exposure was assessed as the sum of inorganic arsenic, monomethylarsonate and dimethylarsinate levels (ΣAs). LTL was measured by quantitative polymerase chain reaction. Results: In the SHS, median levels were 1.09 for LTL, and 8.8, 1.01 and 0.11 μg/g creatinine for ΣAs, Cd, and W, respectively. In the SHFS, median levels were 1.01 for LTL, and 4.3, 0.44, and 0.10 μg/g creatinine. Among SHS participants, increased urine ΣAs, Cd, and W was associated with shorter LTL. The adjusted geometric mean ratio (95% confidence interval) of LTL per an increase equal to the difference between the percentiles 90th and 10th in metal distributions was 0.85 (0.79, 0.92) for ΣAs, 0.91 (0.84, 1.00) for Cd and 0.93 (0.88, 0.98) for W. We observed no significant associations among SHFS participants. The findings also suggest that the association between arsenic and LTL might be differential depending on the exposure levels or age. Conclusions: Additional research is needed to confirm the association between metal exposures and telomere length. Graphical abstract: Geometric Mean Ratio of leukocyte telomere length by urine arsenic ( ∑ As ), cadmium (cd) and tungsten (W) levels in the Strong Heart Study (N = 1702) and the Strong Heart Family Study (N = 1793). Image 1 Highlights: The cellular mechanisms for metal-related health effects are not fully understood. The Strong Heart and Strong Heart Family studies have telomere and urine metal data. Arsenic, cadmium and tungsten were related with shorter telomeres in SHS (median age 55). In the SHFS (median age 37), the corresponding associations were null. Additional research is needed to confirm the association of metal exposures with telomere length.